Nephrogeriatric patients in standard chronic hemodialysis program - Padrón Ortega, Dailan; Candelaria Brito, Julio César; Gutiérrez Gutiérrez, Carlos; Acosta Pérez, Dulce María; Barredo Hernandez, Yadiel (Revista Cubana de Nefrología, 2024)
Introduction: the number of nephrogeriatric patients due to stage 5 chronic kidney disease who require replacement therapies for renal function is progressively increasing throughout the world. Objective: to clinically characterize nephrogeriatric patients in a chronic hemodialysis program. Method: observational, descriptive and cross-sectional study, in the Consolación del Sur municipality, in the period 2020 to 2022. The universe consisted of 46 patients and the sample of 38, who met the established inclusion and exclusion criteria. A questionnaire was used to collect the information, which included variables such as comorbidities, signs and symptoms at the beginning of the diagnosis of the disease, presence of chronic anemia, vascular access and frequent intradialytic morbidity. Descriptive statistical methods expressed in absolute frequencies and relative frequencies were used. Ethical aspects were met. Results: the main comorbidity associated with CKD was hypertension with 21 patients representing 55.2%, the most frequent sign at the time of diagnosis was edema and the main referred symptom was anorexia, both with 29 patients (76.3%), the presence of anemia was observed in 31 patients (81.5%). The most used vascular access was the arteriovenous fistula (AVF) in 36 patients (94.7%). The development of frequent intradialytic morbidities was observed in 44.7% Conclusions: nephrogeriatric patients who are part of the chronic hemodialysis program in the territory were characterized, which allows comprehensive and bidirectional care between primary level physicians and secondary health care. Keywords: nephrogeriatric patients; chronic kidney disease; replacement therapies for renal function; primary health level.